The RNA-binding protein Squid is required for the establishment of anteroposterior polarity in the Drosophila oocyte. - Steinhauer, J.; Kalderon, D. (Development, 2005)
The heterogeneous nuclear ribonucleoprotein (hnRNP) Squid (Sqd) is a highly abundant protein that is expected to bind most cellular RNAs. Nonetheless, Sqd plays a very specific developmental role in dorsoventral (DV) axis formation during Drosophila oogenesis by localizing gurken (grk) RNA. Here, we report that Sqd is also essential for anteroposterior (AP) axis formation. We identified sqd in a screen for modifiers of the Protein Kinase A (PKA) oogenesis polarity phenotype. The AP defects of sqd mutant oocytes resemble those of PKA mutants in several ways. In both cases, the cytoskeletal reorganization at mid-oogenesis, which depends on a signal from the posterior follicle cells, does not produce a correctly polarized microtubule (MT) network. This causes the posterior determinant, oskar (osk) RNA, to localize to central regions of the oocyte, where it is ectopically translated. Additionally, MT-dependent anterior movement of the oocyte nucleus and the grk-dependent specification of posterior follicle cells are unaffected in both mutants. However, in contrast to PKA mutants, sqd mutants do not retain a discrete posterior MT organizing center (MTOC) capable of supporting ectopic posterior localization of bicoid (bcd) RNA. sqd mutants also display several other phenotypes not seen in PKA mutants; these probably result from the disruption of MT polarity in earlier stages of oogenesis. Loss of Sqd does not affect polarity in follicle cells, wings or eyes, indicating a specific role in the determination of MT polarity within the germline.